Improving Product Quality With Production Quality Control - Suhadak; Tedjo Sukmono (PROZIMA (Productivity, Optimization and Manufacturing System Engineering), 2020)
PT. Z is a company engaged in the plastic bag industry. The company produces plastic bags, one of which is a type of ATP 12 x 24 that is often used as plastic wrapping meatballs, sugar and others. A company is certainly required to provide the best quality on its products. To meet the needs and expectations of consumers for the quality of products, the company must improve the quality of existing products. Six sigma is a quality tool that can be used to analyze and process data to maintain or improve the quality of a product based on the process. One of the shorts used in the six sigma method is Define, Measure, Analyze, Improve and Control ( DMAIC). This research focuses on the results of product defects produced for 5 months in 2019. Because of the process analyzed there is data of proportions that are out of control in july and november. So that the data is omitted so that the data can be controlled. The sigma production level of ATP 12 x 24 is currently at the level of 4 sigma so it is necessary to improve to reach the level of 6 sigma. Pareto diagrams and fishbone diagrams can be used as tools to analyze significant factors causing product defects. And it can be known that the causative factor that can be done repair is deflated.